Comparison of Selected Differential‐Producing, Ultrasonic, and Magnetic Flow Meters. Issue 1 (1st January 2016) - Prettyman, Johnny B.; Johnson, Michael C.; Barfuss, Steven L.
Abstract : Selecting the best flow meter for a specific application can be challenging because of the many types and designs of flow meters, with each having its own merits and drawbacks. Illustrating these specific benefits and drawbacks can help the buyer select the meter best suited for the desired application. The flow meters investigated in this research include five designs of differential‐pressure meters (i.e., differential‐producing), a magnetic flow meter, and an ultrasonic flow meter. The differential meters included the Venturi designs, the wedge flow meter, and the V‐cone meter. Testing was completed at the Utah Water Research Laboratory to quantify the accuracy and head loss (pressure loss) of each meter design. The meter longevity and life cycle costs were determined from manufacturer‐supplied information and literature reviews. Although this list is not allinclusive, this study was designed to assist those responsible for selecting a flow meter for their specific application.